A five year review of children with neuroblastoma at dr. Sardjito hospital, Yogyakarta, Indonesia: 1999-2004 - Mulatsih S Sutaryo, Ali K, Purwanto (Berita Kedokteran Masyarakat (BKM), 2005)
Backgraund: The prevalence and outcome of childhood cancers in developing countries is not well documented. In 2001, the Yogyakarta Pediatric Cancer Registry (YPCR) was developed in collaboration with the Saskatchewan Cancer Registry in Canada. Its purpose was to collect and analyze demographic, treatment and outcome data in children newly diagnosed with cancer at Dr. Sardjito General Hospital, Indonesia, Objective: The objectives of this study were to analyze clinical profiles and treatment responses in children under 15 years of age diagnosed with neuroblastoma in 1 January 2000 – 31 December 2004. Materials and Method: A retrospective review of health records was conducted. Information on all patient diagnosed with cancer from 1998 onwards was transcribed onto a standardized data capture form, and then entered into the computerized YCR data base for review and analyses. Result: A total of 27 children with neuroblastoma were identified within the 5 year study period. Twenty two patients (81.5 %) had stage IV disease, 4 (14.8%) had stage II/111, and 1 (3.7%) stage 1. Male to female ratio was 1.5:1. Mean age at diagnosis was 3.1 years. Nineteen patients (70%) were treated on the OPEC protocol, 3 (11%) per the N6 protocol, and 1 (4%) on the NS4E protocol; 4 (15%) were not treated. Of the OPEC treated group, 10 (53%) patients are surviving, 6 (16%) relapsed and 8 (42%) were lost to follow up. Conclusion: In keeping with published reports, the majority of children with neuroblastoma presented with advanced stage disease. The 3-Years free survival was 20% for patients treated on the OPEC protocol. More effective treatment protocols and improved surveillance of children following discharged from hospital are challenges that need to be addressed. Keywords Neuroblastoma-Sardjtio Hospital-outcome